Long Term Follow-Up in a Patient with Arrhythmogenic Right Ventricular Dysplasia - Diana-Aurora BORDEJEVIC; Cristina VACARESCU; Simina CRISAN; Lucian PETRESCU; Tudor Luca CONSTANTIN; Cristian MORNOS; Ciprian RACHIERU; Emilia GOANTA; Dragos COZMA (Sciendo, 2021)
This case report describes eight years of follow-up in a young adult with arrhythmogenic right ventricular dysplasia (ARVD). He presented with exertional palpitations, symmetric T wave inversions and possible epsilon waves in the right precordial leads on electrocardiogram (EKG), raising suspicion for ARVD. Transthoracic echocardiography revealed a dilated and excessively trabeculated right ventricle (RV), and cardiac magnetic resonance imaging showed fatty infiltration of the RV myocardium. These findings established the diagnosis of ARVD, and given his palpitations, a defibrillator was implanted. Over the next years, he had several episodes of ventricular tachycardia requiring therapy from his device, despite escalating medical therapy. He therefore underwent radiofrequency catheter ablation for the VT, which successfully controlled the VT.